Carbon dot crosslinking towards mechanochemically and photochemically induced fluorescence resonance energy transfer. (4th October 2022) - Gao, Wenli; Xiang, Shishuai; Bai, Minghao; Ruan, Yonghong; Zheng, Jinli; Cao, Xuezheng; Xu, Yuanze; Chen, Yinjun; Weng, Wengui
Abstract: Mechanochromism in polymers has attracted great interests in recent years. Herein, we develop a mechanochromic elastomer carrying spiropyran mechanophores in the chain and mechanoresponsiveness of elastomer is enhanced by embedding luminescent carbon dot (CD ) nanoparticles as crosslinkers and energy donor in fluorescence resonance energy transfer (FRET). Compared with the control with physically blended CD, CD crosslinked elastomer exhibit excellent daylight and fluorescent colors change under stretching. The mechanochemically induced fluorescence change is a result of FRET between CD nanoparticles and the activated merocyanine. The control with physically blended CD nanoparticles shows low FRET in stretching due to lower fraction of spiropyran activation as a result of lower mechanical properties. Furthermore, the CD crosslinked elastomer has already been applied in rewritable mechanochemical and photochemical recording or printing. Our demonstration shows that interfacial chemical bonding plays a critical role in the reinforcement of mechanical properties for polymer composites and may exhibit great potential in the study of the acceleration of mechanoresponsiveness of polymer and multi-responsiveness of polymer nanocomposites. Graphical abstract: Image 1 Highlights: Mechanochromic elastomers were prepared with SP being in chain and crosslinked by CD. CD as nanofiller and energy donor improves mechanochromism of nanocomposites by FRET. Elastomers enable use in rewritable mechano- and photochemical recording/printing.